Gut Microbiome Composition Associated With Major Depressive Disorder and Sleep Quality - Zhang, Qi; Yun, Yajun; An, Huimei; Zhao, Wenxuan; Ma, Ting; Wang, Zhiren; Yang, Fude (Frontiers in Psychiatry, 2021)
The microbiota–gut–brain axis plays a critical role in the pathogenesis of major depressive disorder (MDD) and related subclinical symptoms. However, studies on the gut microbiota in MDD are inconsistent, and data on MDD’s effects on sleep lacking. This study aimed to analyze the gut microbiota composition and sleep quality of patients with MDD. We performed 16s rRNA sequencing of stool samples from 36 patients with MDD and 45 healthy controls (HC). Sleep quality was assessed using the Pittsburgh Sleep Quality Index, depressive severity with the Hamilton Depression Scale, and insomnia severity using the Insomnia Severity Index. Forty-eight microbiota targets showed significant differences between MDD and HC. In MDD, six microbiota targets were associated with severity of depression, eleven with sleep quality, and three with sleep severity. At the genus level, Dorea was simultaneously related to depression and sleep quality, while Intestinibacter was more closely related to sleep problems. Coprococcus and Intestinibacter influenced sleep quality independent of severity of depression. In conclusion, the present findings enable a better understanding of the relationship between gut microbiota and MDD-related symptoms. Gut microbiota alterations may become potential biomarkers and/or treatment targets for sleep quality in MDD.